2020
DOI: 10.1039/d0cp00302f
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved, broadband UV-absorption spectrometry measurements of Criegee intermediate kinetics using a new photolytic precursor: unimolecular decomposition of CH2OO and its reaction with formic acid

Abstract: We present a time-resolved broadband cavity-enhanced UV-absorption spectrometer apparatus that we have constructed and utilized for temperature- and pressure-dependent kinetic measurements of formaldehyde oxide (CH2OO) reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(64 citation statements)
references
References 52 publications
3
61
0
Order By: Relevance
“…Experiments were performed using a time-resolved, broadband, cavity-enhanced absorption spectrometer (TR-BB-CEAS) apparatus that is schematically shown in Figure 1 and has been described previously. 19 Acetone oxide was produced homogeneously along the reactor by photolysis of (CH 3 ) 2 CIBr at 213 nm in presence of O 2 ([O 2 ] » [(CH 3 ) 2 CI]).…”
Section: Methodsmentioning
confidence: 99%
“…Experiments were performed using a time-resolved, broadband, cavity-enhanced absorption spectrometer (TR-BB-CEAS) apparatus that is schematically shown in Figure 1 and has been described previously. 19 Acetone oxide was produced homogeneously along the reactor by photolysis of (CH 3 ) 2 CIBr at 213 nm in presence of O 2 ([O 2 ] » [(CH 3 ) 2 CI]).…”
Section: Methodsmentioning
confidence: 99%
“…For example, the reactions of water vapor with syn-MVK-oxide and anti-MACR-oxide were found to be substantially slower than found for alkyl-substituted Criegee intermediates with similar carbon backbones and conformational forms that lack resonance stabilization [12,34]. In contrast, the rate coefficients for reaction of syn-MVK-oxide with formic acid and SO 2 are as large as those for Criegee intermediates such as CH 2 OO [12,14,44,45]. While the barriers for these reactions are comparatively higher than for CH 2 OO, they are strongly submerged relative to reactants such that the rate coefficients for reaction are not greatly impacted.…”
Section: Introductionmentioning
confidence: 94%
“…Calvert et al, 2000). Recent theoretical (Nguyen et al, 2015;Stone et al, 2018;Peltola et al, 2020) works suggest that the only reaction pathway of the bis-oxy radical important under tropospheric conditions is isomerisation to 'hot' formic acid, followed by decomposition to either H2 + CO2 or H2O + CO, in agreement with experimental and theoretical work on acid pyrolysis experiments (Chang et al, 2007;Vichietti et al, 2017). Due to the large excess energy and its small size, very little of the hot acid is stabilised, with measured HCOOH yields from ethene ozonolysis < 5% (Calvert et al, 2000) (and the latter may be due to bimolecular reactions of SCI rather than stabilisation of the hot acid).…”
Section: Ch2oomentioning
confidence: 99%
“…Due to the large excess energy and its small size, very little of the hot acid is stabilised, with measured HCOOH yields from ethene ozonolysis < 5% (Calvert et al, 2000) (and the latter may be due to bimolecular reactions of SCI rather than stabilisation of the hot acid). Stone et al (2018) and Peltola et al (2020) considered the decomposition of stabilised CH2OO using master equation simulations, determining the major decomposition channel to be H2+CO2 (64 % and 61% respectively), with the H2O+CO accounting for the remainder (36%) in Stone et al (2018), while Peltola et al ( 2020) also found a small contribution (~8%) from the OH+HCO channel. It is noted that previous experimental work on ethene ozonolysis (Su et al, 1980;Horie et al, 1991;Neeb et al, 1998) has generally inferred a preference for the H2O+CO channel.…”
Section: Ch2oomentioning
confidence: 99%
See 1 more Smart Citation